The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1182/blood-2015-08-664250
|View full text |Cite
|
Sign up to set email alerts
|

Murine allogeneic CD19 CAR T cells harbor potent antileukemic activity but have the potential to mediate lethal GVHD

Abstract: Key Points Donor-derived allogeneic CAR T cells are functional and eradicate ALL. Allogeneic CD4+ CAR T cells can mediate acute GVHD but only when CD19+ leukemia is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 45 publications
3
73
1
Order By: Relevance
“…Allo-CAR-T may induce severe CRS or GVHD. 17 Citing safety issues from allo-CAR-T infusion because of severe adverse responses, the US Food and Drug Administration terminated 2 phase 1 "off the shelf" CAR-T (UCART123) trials sponsored by Cellectis. Rigorous donor selection or selection of virus-specific allogeneic T cells may reduce these side effects.…”
mentioning
confidence: 99%
“…Allo-CAR-T may induce severe CRS or GVHD. 17 Citing safety issues from allo-CAR-T infusion because of severe adverse responses, the US Food and Drug Administration terminated 2 phase 1 "off the shelf" CAR-T (UCART123) trials sponsored by Cellectis. Rigorous donor selection or selection of virus-specific allogeneic T cells may reduce these side effects.…”
mentioning
confidence: 99%
“…Most EGFRvIII-redirected CAR-T studies were assessed in glioblastoma models. Early preclinical studies demonstrated the potential antitumor effect of first-generation CARs targeting EGFRvIII (González-Navajas et al, 2012;Jacoby et al, 2015). Subsequent second-and third-generation CAR-T cells validated their antitumor activity on EGFRvIII + glioblastoma cells.…”
Section: Egfrviii-specific Car-t Cellsmentioning
confidence: 99%
“…However, production of autologous CAR19 cells from these patients can be difficult as patients frequently have T-cell dysfunction, due to disease and/or treatment-related effects. In this issue of Blood, Jacoby et al 1 addressed this by exploring whether allogeneic donor CAR19 cells could be used to treat ALL-bearing mice using a minor mismatch bone marrow transplant model.…”
Section: Chimeric Antigen Receptor T Cells Redirected To Cd19 (Chimermentioning
confidence: 99%